An interest‐based intervention package to increase peer social interaction in young children with autism spectrum disorder. Issue 1 (30th September 2018) - Watkins, Laci; O'Reilly, Mark; Kuhn, Michelle; Ledbetter‐Cho, Katherine
Abstract : The literature suggests that children with autism spectrum disorder (ASD) educated in inclusive settings generally do not interact with typically developing classmates during social activities. This study assessed whether an intervention package consisting of interest‐based structured play activities involving adult instruction, modeling, and response to child questions would result in an increase in social interaction with typically developing peers. A multiple baseline design across four participants with an embedded reversal was used to demonstrate the effects of the intervention on social interaction during structured play sessions. Initiations, responses, and interactive play increased for all participants. Generalization to novel peers was observed, and treatment gains were maintained during 6‐week follow‐up sessions. Recommendations for practitioners working with children with ASD in inclusive settings and potential areas of future research are discussed.